A Comparative Efficacy Evaluation of Recombinant Topical Thrombin (RECOTHROM®) With A Gelatin Sponge Carrier Versus Topical Oxidized Regenerated Cellulose (TABOTAMP®/SURGICEL®) In A Porcine Liver Bleeding Model - Paul Slezak; Claudia Keibl; Dirk Labahn; Anna Schmidbauer; Yuri Genyk; Heinz Gulle (Journal of Investigative Surgery, 2021)
Purpose Topical hemostatic agents can be classified as active or passive. This study compared the hemostatic efficacy of an active agent, recombinant thrombin (RECOTHROM® [rT]) plus gelatin sponge carrier versus a passive agent, oxidized regenerated cellulose (TABOTAMP®/SURGICEL® [ORC]), in a porcine liver abrasion model. Materials and Methods Eight pigs were used, four of them were heparinized. A total of 80 liver lesions were created, 40 of them in heparinized pigs. Lesions were treated with rT plus gelatin sponge or ORC. Bleeding rate was quantified before treatment by applying pre-weighed gauze. Time to hemostasis was assessed visually for 10 minutes. Results Seven of the 80 lesions were excluded for having initial bleeding rates exceeding the target of 10 g/min. Sixteen and 20 lesions were treated with rT plus gelatin sponge and 19 and 18 lesions were treated with ORC, in non-heparinized and heparinized animals, respectively. Time to hemostasis (median [IQR]) was significantly shorter with rT plus gelatin sponge (30 [30,30] seconds) in heparinized and non-heparinized animals versus ORC in non-heparinized (180 [120,210] seconds) and heparinized animals (215 [135,345] seconds); P < 0.0001 for both comparisons. In heparinized animals, ORC took longer to achieve hemostasis, with treatment failure in 2/18 lesions. Time to hemostasis with ORC was longer for lesions in heparinized animals with initial bleeding rates of >5–10 g/min (285 [225,394] seconds) versus ≤5 g/min (175 [108,290] seconds). Conclusions In this model, rT plus gelatin sponge carrier (active) was a more effective hemostat than ORC (passive) in both heparinized and non-heparinized animals.